Emerging Entities and New Diagnostic Markers for Head and Neck Soft Tissue and Bone Tumors. (May 2021) - Franchi, Alessandro; Thompson, Lester D.R.; Hernandez-Prera, Juan C.; Agaimy, Abbas; Williams, Michelle D.; Mikkelsen, Lauge H.; Bishop, Justin A.; Willems, Stefan M.; Hellquist, Henrik; Ferlito, Alfio
Abstract : Bone and soft tissue tumors of the head and neck are relatively uncommon tumors that often represent a diagnostic challenge because of the wide range of entities that must be considered in the differential diagnosis. Over the past few years, classification of bone and soft tissue tumors has evolved primarily because of substantial contributions from molecular genetics, with the identification of new markers that are increasingly used to complement histopathologic findings in the routine diagnostic workup. This review focuses on the recently described mesenchymal tumors that preferentially involve the head and neck region, with a focus on the most relevant novel immunohistochemical and molecular findings, including gene fusions and mutations, that can help in the diagnosis and in the assessment of clinical behavior.